Probing the Nature of Rotation in the Pleiades, Alpha Persei, and Hyades Clusters - C. J. Hao; Y. Xu; L. G. Hou; S. B. Bian; Z. H. Lin; Y. J. Li; Y. W. Dong; D. J. Liu (The Astrophysical Journal, 2024)
Unraveling the internal kinematics of open clusters is crucial for understanding their formation and evolution. However, there is a dearth of research on this topic, primarily due to the lack of high-quality kinematic data. Using the exquisite-precision astrometric parameters and radial velocities provided by Gaia data release 3, we investigate the internal rotation in three of the most nearby and best-studied open clusters, namely the Pleiades, Alpha Persei, and Hyades clusters. Statistical analyses of the residual motions of the member stars clearly indicate the presence of three-dimensional rotation in the three clusters. The mean rotation velocities of the Pleiades, Alpha Persei, and Hyades clusters within their tidal radii are estimated to be 0.24 ± 0.04, 0.43 ± 0.08, and 0.09 ± 0.03 km s ^−1 , respectively. Similar to the Praesepe cluster that we have studied before, the rotation of the member stars within the tidal radii of these three open clusters can be well interpreted by Newton’s theorem. No expansion or contraction is detected in the three clusters either. Furthermore, we find that the mean rotation velocity of open clusters may be positively correlated with the cluster mass, and the rotation is likely to diminish as open clusters age.